Analysis to Dynamics of Socio-Economic Development of Regions - Babayev, Nusret Salaman-Ogly (International Journal of Criminology and Sociology, 2021)
The article analyzes the dynamics of socio-economic development in the regions in recent years, and the factors that have changed the quantitative and qualitative changes in them. Indicators of the impact of the new economic and social facilities on the living standards of different economic regions and Baku city were also given, including the Theil index and Gini coefficient for economic regions. The article uses systematic analysis, scientific logical summarization, economic classification and other research methods. At the end of the analysis, the relevant findings were substantiated.